2009
DOI: 10.1038/sj.bjc.6605282
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus is associated with breast cancer

Abstract: BACKGROUND: There is increasing evidence that high-risk human papilloma virus (HPV) is involved in cancers in addition to cervical cancer. For example, it is generally accepted that HPV has a role in a significant proportion of head and neck tumours, and it has long been hypothesised that hormone dependent oncogenic viruses, such as HPV may have causal roles in some human breast cancers. A number of reports have identified HPV DNA in breast tissue and breast cancer specimens, but these rely on standard polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
162
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 157 publications
(185 citation statements)
references
References 24 publications
16
162
0
7
Order By: Relevance
“…Only 1 previous study used IS-PCR, which involves amplification, to detect HPV in breast tissue. 7 Those investigators reported that 8 of 31 (31%) breast carcinoma specimens were positive for oncogenic HPV. Seven of these harbored HPV-18, and only 1 of 31 (3.2%) harbored HPV-16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 previous study used IS-PCR, which involves amplification, to detect HPV in breast tissue. 7 Those investigators reported that 8 of 31 (31%) breast carcinoma specimens were positive for oncogenic HPV. Seven of these harbored HPV-18, and only 1 of 31 (3.2%) harbored HPV-16.…”
Section: Discussionmentioning
confidence: 99%
“…In situ molecular methods were used in only 4 studies that investigated the presence of HPV in breast tissues. 4,5,7,8 Three of those studies compared solution PCR and in situ methods for the same set of specimens and identified oncogenic HPV in mammary epithelium of only 4 of 34 (12%) of the collective total, as opposed to 34 of 110 (22%) using standard or nested solution PCR. This raises the possibility that many of the positive results obtained by solution PCR may have been caused by contamination or by the presence of HPV in nonmammary epithelial cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Only three of six MDA-MB-175VII clones isolated apparently contained HPV as indicated by the successful amplification of the L1 region by nested PCR and by in situ PCR as per Heng et al (2009). Interestingly, the HPV-containing clones grew faster than the clones without amplifiable HPV.…”
Section: Sirmentioning
confidence: 97%
“…In response to the lack of detection of HPV in MDA-MB-175VII and SK-Br-3 cell lines, we note that the authors have not followed the methods as set out (Heng et al, 2009). Critically, Peran et al (2010) relied on single rounds of standard and reverse transcription (RT) -PCR.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation